IMPLEMENTATION OF ERP SYSTEMS FOR ACCOUNTING OF MATERIAL RESOURCES IN AGRICULTURE - CHERVIAKOV, Vladyslav (Herald of Khmelnytskyi National University. Economic sciences, 2025)
In the current context of transforming Ukrainian agricultural production and its integration into global economic processes, there is an urgent need to enhance the efficiency of managing material resources within agricultural enterprises. The growing complexity of business operations, the dynamic nature of the agricultural market, and the need for operational control over costs and resources necessitate a transition to modern information management technologies. One of the key tools for the digital transformation of the agricultural sector is ERP (Enterprise Resource Planning) systems, which enable the comprehensive automation of accounting, control, and analysis of material resource usage, ensuring process transparency, integration between structural units, and reducing the reliance on human factors. Accounting for material resources in agriculture is a complex and multi-level process that encompasses the management of procurement, storage, movement, use, and write-off of resources across various units and at different stages of the production cycle. In this context, ERP systems act not only as a means of automating accounting processes but also as a powerful tool for integrated management of enterprise resources. The purpose of this article is to analyze the effectiveness of using ERP systems for accounting for material resources at agricultural enterprises, and to identify opportunities and barriers in formulating practical recommendations for their implementation. During the research process, methods of analysis and synthesis, comparison, theoretical and logical generalization were employed. The methodological basis was the dialectical research method. The article highlights the theoretical foundations of the functioning of ERP systems in Ukraine and the conditions for their adaptation to agricultural specifics; characterizes the main functional blocks of accounting for material resources in ERP systems; identifies the main barriers to the implementation of ERP systems at enterprises in Ukraine, among which are the high cost of implementation, the complexity of adaptation to agricultural specifics, the insufficient level of digital competence of personnel and limited technical support; A set of practical recommendations has been developed that will facilitate the effective use of ERP systems for accounting for material resources, the effective implementation of which is possible only with a systematic approach, a combination of technical, organizational and methodological components.